2022
DOI: 10.2166/nh.2022.022
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization of flow duration curves in Colombia

Abstract: It is essential to know the streamflow behavior in hydrological basins for appropriate water resource planning and management. In Colombia, where there is a considerable water resource potential, there is a need to generate hydrological modeling for many ungauged catchments. Thus, this study presents the regionalization of flow duration curves (FDC) in Colombia. Daily flow time series from 655 gauging stations were used to define homogenous hydrological regions, considering geological, topographic, and climati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These agree with Adeyeri et al [75] and [78], who reported separately that over land in the dry season with minimum high flows, there is a positive correlation between precipitation and temperature due to the low moisture-holding capacity of the atmosphere. The estimation of flows is very critical, especially in the ungauged river basins, and it has been a big challenge for the hydrologist from a planning and management perspective [65,79,80]. The FDC form resulted from the geomorphological attributes and their interrelations [81], which are very complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These agree with Adeyeri et al [75] and [78], who reported separately that over land in the dry season with minimum high flows, there is a positive correlation between precipitation and temperature due to the low moisture-holding capacity of the atmosphere. The estimation of flows is very critical, especially in the ungauged river basins, and it has been a big challenge for the hydrologist from a planning and management perspective [65,79,80]. The FDC form resulted from the geomorphological attributes and their interrelations [81], which are very complex.…”
Section: Discussionmentioning
confidence: 99%
“…The flow duration curve indicates flow availability and the percentage of the equal or exceedance over a specific period in that river basin [57][58][59]. FDCs have been widely used in almost all types (i.e., mountainous, cold regions, semi-arid to arid regions) of river basins for hydrological analysis [60][61][62][63][64][65][66]. Generally, any FDC graph contains the flow on the Y-axis, whereas the X-axis includes the number of days exceedance from a particular flow-relative percentile flow [57,58].…”
Section: Flow Duration Curves (Fdc)mentioning
confidence: 99%